Updates on Prevalence and Trend Status of Visceral Leishmaniasis at Two Health Facilities in Amhara Regional State, Northwest Ethiopia: A Retrospective Study - Mulat Yimer; Endalkachew Nibret; Gizachew Yismaw (Biochemistry Research International)
Ethiopia is one of the countries accounted for over 90% of annual visceral leishmaniasis incidence. Despite this, yet there are no active and passive surveillance activities in the Amhara Region that will give up-to-date information about the disease status at the health facility levels. Therefore, this study aimed to report up-to-date information about visceral leishmaniasis and its trend status at two health facilities and the surrounding areas. A retrospective study from October 2017 to May 2021 was conducted by reviewing patient records at Metema and Addis Zemen Hospitals. Data on Sex, age, occupation, residence, month, year, and rK39 test results were collected using a questionnaire and were analyzed using Statistical Package for Social Sciences (SPSS) version 20. The chi-square test was used to see the association between variables. p < 0.05 was considered as statistically significant. Of the 2,703 visceral leishmaniasis suspected cases diagnosed with the rK39 test, 877 (32.4%) were confirmed (positive) cases. Monthly and yearly trends depicted that the largest number of suspected cases was reported in October and 2018, respectively. Daily laborers were the most affected individuals in Metema areas.